2019
DOI: 10.14302/issn.2637-6075.jpae-19-3074
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metals Contamination of Water and Cupscale Grass (Sacciolepisafricana) along the Epie Creek in Bayelsa State, Nigeria

Abstract: This study was conducted to investigate the concentration of three heavy metals; iron, chromium and lead in surface water and plant (Sacciolepisafricana) tissues along the Epie creek. This was aimed at determining the heavy metal loading of surface waters and the extent of bioaccumulation in the most prevalent grass species found growing within the river course. Metals were determined using atomic absorption spectrophotometer. Result of water analysis recorded the least and most significant iron concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Iron, though considered essential nutrient, can also be a contaminant in water. Elevated threshold levels of iron found in Epie creek (Yenagoa, Bayelsa State) was attributed to anthropogenic inputs such as soil and dumpsite leachates, which lowered the clarity and increased turbidity of the aquatic environment, making the water unsafe for human consumption [10]. [11], in their research work titled 'the potability of groundwater in Bayelsa State, central Niger Delta, Nigeria: a review' concluded that the physicochemical parameters of some acclaimed potable water (including heavy metals like iron) were above the Standards Organization of Nigeria (SON) and the World Health Organization (WHO) recommended limits.…”
Section: Introductionmentioning
confidence: 99%
“…Iron, though considered essential nutrient, can also be a contaminant in water. Elevated threshold levels of iron found in Epie creek (Yenagoa, Bayelsa State) was attributed to anthropogenic inputs such as soil and dumpsite leachates, which lowered the clarity and increased turbidity of the aquatic environment, making the water unsafe for human consumption [10]. [11], in their research work titled 'the potability of groundwater in Bayelsa State, central Niger Delta, Nigeria: a review' concluded that the physicochemical parameters of some acclaimed potable water (including heavy metals like iron) were above the Standards Organization of Nigeria (SON) and the World Health Organization (WHO) recommended limits.…”
Section: Introductionmentioning
confidence: 99%